2011
DOI: 10.1161/circulationaha.110.972406
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Structure of the Aortic Valve and Ascending Aorta in Adults Having Aortic Valve Replacement for Aortic Stenosis Versus for Pure Aortic Regurgitation and Resection of the Ascending Aorta for Aneurysm

Abstract: Background-There is debate concerning whether an aneurysmal ascending aorta should be replaced when associated with a dysfunctioning aortic valve that is to be replaced. To examine this issue, we divided the patients by type of aortic valve dysfunction-either aortic stenosis (AS) or pure aortic regurgitation (AR)-something not previously undertaken. Methods and Results-Of 122 patients with ascending aortic aneurysm (unassociated with aortitis or acute dissection), the aortic valve was congenitally malformed (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 31 publications
6
57
1
1
Order By: Relevance
“…22 Furthermore, dilation of the aortic root and the ascending aorta can alter aortic leaflet stress and thereby affect coaptation of an otherwise normal aortic valve, 23 resulting in significant aortic regurgitation as revealed by echocardiography. This is consistent with the observations of Roberts and colleagues, 24,25 who reported, in the histologic specimens of patients with Marfan syndrome, severe loss of medial elastic fibers in the sinuses of Valsalva and in the ascending aorta. In addition, the findings of myxomatous involvement of the aortic valve suggest that surgical decisions regarding the aortic valve in patients with Marfan syndrome should not arise only from the echocardiographic appearance of the valve.…”
Section: Ao = Aorta; La = Left Atrium; LV = Left Ventriclesupporting
confidence: 93%
“…22 Furthermore, dilation of the aortic root and the ascending aorta can alter aortic leaflet stress and thereby affect coaptation of an otherwise normal aortic valve, 23 resulting in significant aortic regurgitation as revealed by echocardiography. This is consistent with the observations of Roberts and colleagues, 24,25 who reported, in the histologic specimens of patients with Marfan syndrome, severe loss of medial elastic fibers in the sinuses of Valsalva and in the ascending aorta. In addition, the findings of myxomatous involvement of the aortic valve suggest that surgical decisions regarding the aortic valve in patients with Marfan syndrome should not arise only from the echocardiographic appearance of the valve.…”
Section: Ao = Aorta; La = Left Atrium; LV = Left Ventriclesupporting
confidence: 93%
“…Aortic regurgitation is an additional risk factor for aortopathy1; however, it is difficult to quantify diastolic WSS attributed to low signal‐to‐noise ratio with 4D flow MRI and the need for a time resolved segmentation to capture aortic root motion. Given the results from previous studies showing the greatest flow differences between patient groups occur at systole,29 we chose to focus on systolic WSS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Benedik and colleagues evaluated the histological and mechanical characteristics of the aortic wall in patients who underwent aortic stenosis or regurgitation surgery and showed that the latter group had a worse quality and a superior thickness of the ascending aorta than the former 35 . Roberts and colleagues observed, in histological sections of ascending aortas, only a minimal loss of medial elastic fibers in the aortic media of patients with aortic stenosis compared to severe elastic fibers damage reported in patients with aortic regurgitation 36 .…”
Section: Clinical Features Associated With Bavmentioning
confidence: 98%
“…Interestingly, 8 out of our 10 patients displayed this phenotype, in association with a certain degree of systemic features typical of connective tissue disorders 11 . Finally, the 2 patients bearing FBN1 mutations had significant aortic regurgitation, which is a powerful predictor of loss of aortic medial elastic fibers in patients with ascending aortic aneurysms and aortic valve disease 35,36 . These findings call for greater focus on the BAV-related cardiovascular abnormalities rather than on the MFS-like systemic features, which may well coexist and warrant investigation in BAV patients in general, but are not associated with the FBN1 mutations identified in the present study.…”
Section: Marfan Syndrome Bav and Fbn1 Mutationsmentioning
confidence: 98%